2008
DOI: 10.3844/ajabssp.2008.444.450
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Permeation Studies between Scale Region of Shed Snake Skin and Human Skin In vitro

Abstract: Scales of shed king cobra (Ophiophagus hannah) skin from the dorsal portions, (SSS) and human breast epidermis (HE) were used as barrier membranes for comparison in an in vitro drug permeation study of nine active compounds (MW range 150-300 g mol -1 , pK a 3-10). Each compound, saturated in a donor solution at pH 4.0 or 5.6, permeated through the barrier membrane, fully hydrated. A receptor solution at pH 7.4 was sampled for quantification at its λ max by UV-Visible spectrophotometry and/or HPLC. The permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
1
Order By: Relevance
“…It consists of three layersbeta, meso, and alpha layers -and is composed of two very different regions -scales and separating these, hinges; the scales are firm, while the hinges are soft. 62 From Table 5, it could be concluded that the amount of OLM permeated from the formulae (TFs and TE14) was significantly higher than the amount permeated from OLM suspension (P#0.05). However, it was noticed that OLM permeated through both membranes in the same order: TE14 .…”
Section: Measurement Of Vesicles' Elasticitymentioning
confidence: 92%
“…It consists of three layersbeta, meso, and alpha layers -and is composed of two very different regions -scales and separating these, hinges; the scales are firm, while the hinges are soft. 62 From Table 5, it could be concluded that the amount of OLM permeated from the formulae (TFs and TE14) was significantly higher than the amount permeated from OLM suspension (P#0.05). However, it was noticed that OLM permeated through both membranes in the same order: TE14 .…”
Section: Measurement Of Vesicles' Elasticitymentioning
confidence: 92%
“…The cyan dotted lines show permeability coefficients according to the pH-partition hypothesis 8 based on the calculated permeability coefficient of the neutral state. The experimental values are from Singh and Roberts, 54 Chantasart et al, 55 Priprem et al, 56 Roy and Flynn, 57 Michaels et al, 58 Uchida et al, 59 Morimoto et al, 60 Zorin et al, 61 Qvist et al, 62 and Smith and Irwin. 63 …”
Section: Results and Discussionmentioning
confidence: 99%
“…It can also be seen that the permeability coefficients of the acidic compounds, diclofenac, naproxen, and salicylic acid, are predicted to be more sensitive to the pH of the donor solution/formulation. Under in vitro conditions, this would correspond to an observation of a relatively higher permeability of the ionized species of the basic compounds, since they are in 54 Chantasart et al, 55 Priprem et al, 56 Roy and Flynn, 57 Michaels et al, 58 Uchida et al, 59 Morimoto et al, 60 Zorin et al, 61 Qvist et al, 62…”
Section: ■ Conclusionmentioning
confidence: 96%
“…Since then, multiple studies performed in the subject have shown that there is correlation between human skin and moulted snake skin with regard to their permeation and cutaneous penetration, despite the anatomical and chemical differences between them. Priprem et al (2008) compared the permeation of various compounds through the moulted skin of a king cobra and the human epidermis; their results were similar between the two membrane models [15][16][17].…”
Section: Discussionmentioning
confidence: 99%